Teknik Stimulasi Kemampuan Literasi Awal Anak Prasekolah Oleh Ibu Di Rumah - FITRIYANI, NUR ROHMI (2016)
THE TECHNIQUE OF EARLY LITERACY ABILITY STIMULATION IN PRESCHOOL CHILDREN BY MOTHERS AT HOME Nur Rohmi Fitriyani Dr. Lisnawati Ruhaena, S.Psi, M.Si, Psi Nurrohmi13@yahoo.com Psychology Faculty, Muhammadiyah University of Surakarta ABSTRACT The early literacy ability is one of abilities that must be began to be taught to the early-age children. It was very important as a trigger in predicting the children's ability in future. In fact, recently, there are many children who have not had an interest in the early literacy, besides, it also make mothers pay much attention related to the children's literacy ability. One of evidences of mothers' attention is mothers' enthusiasm in attending a training of multisensory technique. Based on the training, it was obtained results that the mothers' understanding was increased related to the technique of literacy stimulation and the children felt comfortable on the technique of literacy stimulation given by the mothers. Nevertheless, in another side, a question was raised on how the mothers implement the technique of early literacy stimulation to the children at home. This research aimed at understanding on the ways of mothers in implementing the technique of early literacy ability stimulation to the preschool children at home. The determination of participants was selected based on the previously determined criteria, that was mothers who had ever attended the training of early literacy stimulation. Based on the criteria, the researcher selected 6 participants. The method of research used a qualitative approach through the data collection in the forms of interview, observation, and daily notes. Based on the results of data analysis, it could be concluded that the technique of early literacy ability stimulation that the mothers conducted was appropriate to the stages of the technique of literacy stimulation previously taught, besides, it was also found that the technique of writing together was effective in increasing the children's writing ability. Keywords : Technique of stimulation, Early literacy, Mother